2014
DOI: 10.1111/jth.12678
|View full text |Cite
|
Sign up to set email alerts
|

Differential risks in men and women for first and recurrent venous thrombosis: the role of genes and environment

Abstract: To cite this article: Roach REJ, Cannegieter SC, Lijfering WM. Differential risks in men and women for first and recurrent venous thrombosis: the role of genes and environment. J Thromb Haemost 2014; 12: 1593-600.Summary. Men have a higher risk of first and recurrent venous thrombosis than do women. However, the pathophysiology underlying this phenomenon is as yet unknown. In this review article, we assessed the prevalence and strength of genetic and acquired risk factors for venous thrombosis for men and wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
101
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(117 citation statements)
references
References 82 publications
12
101
0
Order By: Relevance
“…Most previous studies have reported a two‐fold to four‐fold higher recurrence rate among men than among women . In our study, we confirmed this trend, but the relative risk of recurrence was only 30% higher in men than in women, and the difference was not statistically significant.…”
Section: Discussionsupporting
confidence: 83%
“…Most previous studies have reported a two‐fold to four‐fold higher recurrence rate among men than among women . In our study, we confirmed this trend, but the relative risk of recurrence was only 30% higher in men than in women, and the difference was not statistically significant.…”
Section: Discussionsupporting
confidence: 83%
“…Our results showed a higher rate of SVT in men (89.4%, P = 0.007), which is in agreement with the study of Roach et al who recently showed a higher risk of first and recurrent venous thrombosis in male patients. 16 SVT was also more common in our patients who smoked (P = 0.003). Smoking, especially heavy smoking, is a known risk factor for thrombosis.…”
Section: Discussionmentioning
confidence: 51%
“…2 Splanchnic vein thrombosis (SVT) is a typical complication of AP, occurring in 1. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22].6% of the cases. 1,5 It is usually discovered either incidentally on CT scan that is performed to assess the severity of the pancreatitis or during the follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…Differential risks in men and women for first and recurrent venous thrombosis: the role of genes and environment: reply We would like to thank Xu and Schooling for their comment containing an interesting meta-analysis in which they showed that patients treated with exogenous testosterone had an almost 5-fold increased risk of venous thrombosis [1]. Although we agree that this result adds credence to the hypothesis that exogenous testosterone increases venous thrombosis risk, for a number of reasons, it still seems unlikely that a difference in endogenous testosterone levels between men and women can explain the sex difference for venous thrombosis.…”
Section: Marin 1993mentioning
confidence: 99%